Studi Hubungan Kerapatan Vegetasi Lamun dengan Laju Sedimentasi di Perairan Teluk Awur dan Bandengan Jepara Pada Periode Juni – Juli 2012 - Nursanti, Nursanti; Riniatsih, Ita; Satriadi, Alfi (977-2407769)
Teluk Awur and Bandengan waters are located in Jepara which have different conditions and also the waters are still good for seagrass growth. Seagrass has one physical function as a sediment catcher in coastal waters. The sedimentation rate in the Teluk Awur and Bandengan waters affected by seagrass density, flow velocity, and sediment composition. The purpose of this research is to determine the relationship of seagrass vegetation density with the rate of sedimentation in the Teluk Awur and Bandengan waters, Jepara. This reaserch was conducted in June-July 2012. in the Teluk Awur waters discovered 6 genus such as Enhalus, Thalassia, Thalassodendron, Cymodocea, Halodule, and Syringodium, with an average value of density 198.03 individu/m2. While Bandengan waters was found 7 genus such as Enhalus, Thalassia, Thalassodendron, Cymodocea, Halodule, Syringodium and Halophila, with average value of density 457.1 individu/m2. The results showed that the average value of sedimentation rate in the Teluk Awur waters 438.74 g/m2/week, while the Bandengan waters 667.42 g/m2/week. The R2 value of relationship between Seagrass density with the sedimentation rate in the Teluk Awur waters 0.566. While the R2 of Bandengan waters 0.073. The Teluk Awur waters contain a little lanau sediment so it has a little sedimenation. Bandengan waters contain higher lanau sediment so it has more sedimentation.